Gender Representation and Social Values in Arabic Language Workbooks for MTs Student: A Critical Discourse Analysis - Saripah, Saripah; Muizzudin, Moch.; Syahid, Ahmad Habibi (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2026)
LKS as one of the most widely used teaching materials, functions not only as a medium for practicing language skills but also as a tool for socializing social values and gender representation. However, LKS often contain representations that are not neutral; instead, they reflect ideologies, norms, and power relations that prevail in society. Therefore, it is important to conduct a critical study to understand how gender representation and social values are presented in Arabic Language LKS, as well as their implications for the character education process of students. This study aims to analyze gender representation and social values in Arabic Language LKS for Islamic Junior High Schools (MTs) using Fairclough’s Critical Discourse Analysis (CDA) approach. The data were obtained through an in-depth review of reading texts, dialogues, illustrations, and exercises contained in the LKS. The analysis was conducted by mapping the gender roles displayed and identifying the social values embedded in the texts. The findings show that gender representation in Arabic Language LKS for MTs tends to remain biased, reinforcing traditional male roles in the public sphere and female roles in the domestic sphere. Meanwhile, the social values presented prominently emphasize aspects of religiosity, politeness, responsibility, and cooperation but pay less attention to themes of diversity, social justice, and gender equality. These findings indicate that the future development of Arabic Language LKS needs to pay greater attention to the principles of gender equality and the integration of more inclusive and progressive social values. Thus, this study provides an important contribution to the development of teaching materials that not only strengthen students’ language competence but also encourage the formation of fair, open-minded characters with a sense of social justice, in line with the spirit of the Merdeka Curriculum.